2019
DOI: 10.1155/2019/5613417
|View full text |Cite
|
Sign up to set email alerts
|

miR-199a-5p Represses Protective Autophagy and Overcomes Chemoresistance by Directly Targeting DRAM1 in Acute Myeloid Leukemia

Abstract: Chemotherapy resistance is still a primary clinical obstacle to the successful treatment of acute myeloid leukemia (AML). The underlying mechanisms of drug resistance are complicated and have not been fully understood. Here, we found that miR-199a-5p levels were significantly reduced in refractory/relapsed AML patients compared to those who achieved complete remission after chemotherapy. Consistently, miR-199a-5p was markedly decreased in Adriamycin-resistant AML K562/ADM cells in contrast with Adriamycin-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
0
17
4
Order By: Relevance
“…Previous studies have reported the downregulation of miR-199a-5p levels in drug-resistant cell lines compared with those in the corresponding parental cell lines (19)(20)(21). However, the present study was the first to reveal that the levels of miR-199a-5p were upregulated in MDR lung cancer cells compared with those in the parental cell lines.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Previous studies have reported the downregulation of miR-199a-5p levels in drug-resistant cell lines compared with those in the corresponding parental cell lines (19)(20)(21). However, the present study was the first to reveal that the levels of miR-199a-5p were upregulated in MDR lung cancer cells compared with those in the parental cell lines.…”
Section: Discussioncontrasting
confidence: 69%
“…However, the present study was the first to reveal that the levels of miR-199a-5p were upregulated in MDR lung cancer cells compared with those in the parental cell lines. In the present study, RT-qPCR results demonstrated that the levels of miR-199a-5p were upregulated in PTX-resistant A549/T cells compared with those in the parental cells, which was different from imatinib-resistant K562, cisplatin-treated MG63 and Adriamycin-resistant K562 cells in previous studies (19)(20)(21). These results suggested that the effects of miR-199a-5p on MDR induction were cell line-specific.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Upregulation of DRAM1 has been associated with increased levels of irradiation-induced autophagy in breast cancer cells 41 . While downregulation of DRAM1 gene suppressed autophagy and increased chemosensitivity of acute myeloid leukemia (AML) cells 42 . In the present study, we found that FTSJ1 could interact with DRAM1 in NSCLC cells, our findings underscored the complicity of tRNA modifications and their regulatory enzymes in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs participate in the regulation of various biological events, including tumor growth, invasion, metastasis and angiogenesis ( 15 ). miRNA (miR)-199a-5p belongs to the miR-199a family, which has been demonstrated to participate in the progression of multiple diseases such as acute myeloid leukemia ( 16 ) and cervical cancer ( 17 ). Dai et al ( 18 ) reported that miR-199a-5p prevented hepatocyte damage induced by bile acid.…”
Section: Introductionmentioning
confidence: 99%